If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9n + -2 + -3m = 8 + -4m Reorder the terms: -2 + -3m + 9n = 8 + -4m Solving -2 + -3m + 9n = 8 + -4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4m' to each side of the equation. -2 + -3m + 4m + 9n = 8 + -4m + 4m Combine like terms: -3m + 4m = 1m -2 + 1m + 9n = 8 + -4m + 4m Combine like terms: -4m + 4m = 0 -2 + 1m + 9n = 8 + 0 -2 + 1m + 9n = 8 Add '2' to each side of the equation. -2 + 1m + 2 + 9n = 8 + 2 Reorder the terms: -2 + 2 + 1m + 9n = 8 + 2 Combine like terms: -2 + 2 = 0 0 + 1m + 9n = 8 + 2 1m + 9n = 8 + 2 Combine like terms: 8 + 2 = 10 1m + 9n = 10 Add '-9n' to each side of the equation. 1m + 9n + -9n = 10 + -9n Combine like terms: 9n + -9n = 0 1m + 0 = 10 + -9n 1m = 10 + -9n Divide each side by '1'. m = 10 + -9n Simplifying m = 10 + -9n
| 5*-32= | | x^3-x+6=0 | | 7(8b+12)=700 | | 9s-11=31s | | 7x-5=7x+6 | | x^2+10x-4= | | x^3+x^2+13x+4=0 | | 2x+6(x-3)=150 | | 46=-9x+10 | | 12x+8=-8+13x | | 4(3b+5)=104 | | 0.3x+12.9=4.6x | | 4x-25x= | | 8x-20=4-11 | | -(2x-x)=0 | | 9x-15=3x-3 | | 3b-6+6b=43+2b | | 6(7x+7)=336 | | -3x+10=10-3x | | 50+0.4p=30+0.8p | | 4x-(3x+6)=-1 | | x/7=x/4+8 | | 7x+9=2x+18 | | 8(5b+2)=496 | | x-34=13 | | -95=5(1-5k) | | 2x^4+3x^2-1=0 | | -1/3+z=2/3 | | x+5=22 | | 5n(2-n)=-11 | | x+6=2x-6 | | -353=5(3+8x)+6 |